Dimensioning of Auxiliaries for a Single-Cylinder Research Engine - Strang, Anna-Stina (My University, 2018)
The most important part of Wärtsilä’s internal combustion engine research is engine testing. While conventional multi-cylinder engine testing provides comprehensive engine research, single-cylinder engine testing enables advanced combustion process research that is more challenging to perform with a multi-cylinder engine. A small-bore medium-speed single-cylinder research engine located in the Wärtsilä Vaskiluoto Engine Laboratory will be transferred to Vaasa Energy Business Innovation Centre (VEBIC). The purpose of this thesis work was to give a general view of single-cylinder engine testing and its requirements. Engine auxiliaries as well as control and measurement systems of the single-cylinder engine were examined. Resourcing and operational aspects of single-cylinder engine testing were discussed, and the single-cylinder engine test cell layout in Wärtsilä Vaskiluoto Engine Laboratory was presented. Space requirements for engine-related mechanical and electrical systems were grouped with the purpose of designing the test cell at VEBIC. Also the internal combustion engine research targets of VEBIC were reviewed. The most important goal of the thesis work was to create a dimensioning guide for the auxiliaries of a single-cylinder engine. A dimensioning summary table was made only for a single-cylinder engine with a certain nominal power by applying four dimensioning criteria. However, the dimensioning criteria introduced in this thesis can be applied to a single-cylinder engine with any nominal power for the purpose of dimensioning its auxiliaries.
Keywords: Internal combustion engine; single cylinder engine; testing; auxiliary; dimensioning; fi=Energiatekniikka|en=Energy Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|